Prevalence of Respiratory Polyomaviruses Among Pediatric Patients With Respiratory Symptoms in Singapore - Hansen-Estruch, Christophe; Coleman, Kristen K.; Thoon, Koh C.; Low, Jenny G.; Anderson, Benjamin D.; Gray, Gregory C. (Frontiers in Pediatrics, 2018)
Background: Although WU polyomavirus (WU) and KI polyomavirus (KI) have been demonstrated to infect the human respiratory tract, it remains unclear if WU or KI cause human disease. We sought to further investigate the relationship between WU and KI infection and respiratory disease in a pediatric population with respiratory symptoms in Singapore. Methods: We conducted a cross-sectional study of pediatric patients with respiratory symptoms in a Singaporean pediatrics hospital. Upon consent, residual respiratory samples from pediatric inpatients, previously screened for common respiratory viruses, were collected and further screened for WU and KI using qPCR. The amplicons of positive samples were sequenced for confirmation. The severity of a patient's illness was assessed by chart review post-discharge looking for clinical markers of respiratory status such as presenting symptoms, diagnoses, and interventions. Results: From December 2016 to April 2017, 201 patients with residual respiratory samples were enrolled in the study. The average age of all participants recruited was 45 months. WU and KI were detected in 13% (26/201) and 3% (6/201) of patients, respectively. Conducting bivariate and multivariate modeling, patients with WU or KI positivity were not at increased risk of SARI, need for additional oxygen, intravenous fluids, and did not receive additional oral antibiotics or bronchodilators during admission. In contrast, patients with RSV detections were at increased risk of requiring supplemental oxygen during hospital admission. Conclusion: While limited in sample size, our pilot study data do not support the hypothesis that molecular evidence of WU or KI was associated with increased morbidity among a sample of general, pediatric patients with respiratory illness in Singapore.